Electron–phonon coupling in hybrid lead halide perovskites - Adam D. Wright (Nature Portfolio, 2016)
Phonon scattering limits charge transport in perovskite solar cells, yet the interactions involved are still poorly understood. Here, Wright et al. show by photoluminescence measurements and first-principles calculations that longitudinal optical phonons dominate the electron-phonon coupling at room temperature.